Changes in gross motor function in children with cerebral palsy and associated factors - Hidayah, Nurul; Widodo, Dwi Putro; Mangunatmadja, Irawan; Handryastuti, Setyo (Paediatrica Indonesiana, 2026)
Background Cerebral palsy (CP) is a condition characterized by abnormalities in movement, muscle tone, and posture caused by non-progressive damage to immature brain tissue. Gross motor function is associated with the quality of life and prognosis of children with CP. Objective To observe gross motor changes in cerebral palsy patients based on GMFCS from the time of initial diagnosis compared to the current GMFCS. Methods This was a cross-sectional study with subjects classified into two groups based on GMFCS at the time of CP diagnosis and at the time of the study (April 2018). Group 1 consisted of level I-III GMFCS and group I consisted of level IV-V GMFCS. Data were obtained from the results of two GMFCS measurements: at diagnosis by history-taking and at the time of this study by physical examination. Subjects were 100 children who met the inclusion criteria who were treated at the Child Neurology Polyclinic and the Medical Rehabilitation Polyclinic, FKUI-RSCM. Results The most common characteristics in our CP patients were male gender (61%), full term birth (75%), tetraplegia CP type (66%), abnormal CT findings (83.3%), abnormal head circumference (83%), and epilepsy (61%). There was a significant gross motor skill improvement between the time of initial diagnosis and current gross motor skills (P<0.001) and no subjects had deteriorated. This improvement was influenced by factors such as better outcomes in females compared to males, diplegia-type cerebral palsy compared to tetraplegia, and normal vs. abnormal CT findings. Conclusion Gross motor improvement in children with cerebral palsy varies significantly from initial diagnosis, with better outcomes observed in females, those with diplegia, and those with normal CT findings.